2021
DOI: 10.1093/tas/txab021
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining continuity of nutrient intake after weaning. I. Review of pre-weaning strategies

Abstract: Weaning is a crucial phase of swine production marked by a multitude of biological and environmental stressors, which have a significant impact on immediate post-weaning behavior and feed intake (FI). During this time the piglet’s gastrointestinal (GI) system is also undergoing extensive epithelial, immune and nervous system development. In this review, our objective is to describe the different pre-weaning strategies that can be used to minimize nutrient intake disruption and improve FI in the immediate post-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 81 publications
0
12
0
Order By: Relevance
“…Nursing by the sow is often complemented with plant-based milk replacers to account for big litter sizes in commercial settings as early as day 2 of life [63]. Especially when the number of piglets surpasses the number of functional teats, offering milk replacer allows the surplus piglets to stay with their own mother, while providing extra nutrition and a certain training of the intestine to solid feed components preweaning.…”
Section: Lipids and Bioactive Fa In Milk Replacers And Solid Dietsmentioning
confidence: 99%
“…Nursing by the sow is often complemented with plant-based milk replacers to account for big litter sizes in commercial settings as early as day 2 of life [63]. Especially when the number of piglets surpasses the number of functional teats, offering milk replacer allows the surplus piglets to stay with their own mother, while providing extra nutrition and a certain training of the intestine to solid feed components preweaning.…”
Section: Lipids and Bioactive Fa In Milk Replacers And Solid Dietsmentioning
confidence: 99%
“…Provide supplemental feeding with replacement milk in the pre-weaning period for sows with large litters and/or poor milk production. [26,31,36] Vaccination of sows…”
Section: Creep-feedingmentioning
confidence: 99%
“…The only exception, of course, is the gestating sow which is normally limit fed. One of the most difficult times to achieve maximum feed intake occurs in the first week post weaning ( Wensley et al, 2021a , b ). Bruininx et al (2001) reported that only about 50% of pigs have eaten within 4 h of weaning, with a quarter failing to eat during the first 24 h after weaning.…”
Section: Management Strategies To Improve Abf Productionmentioning
confidence: 99%